(untitled) (Revista Contexto & Educação, 2025)
The concept of equity goes beyond the constitutional and legal principle of equality, which is general in nature and advocates for equality before the law. Equity is an ethical principle that serves as an essential tool for recognizing and respecting differences through public policies guided by the principles of justice and inclusion. It seeks fair equality by promoting unequal treatment for unequal individuals in proportion to their inequalities. This study aims to explore the concept of equity as applied to Special Education, differentiating it from the concept of equality, considering the right to education for persons with disabilities and the State’s duty to establish inclusive educational systems (Aristóteles, 1991; Abbagnano, 2000; Azevedo, 2013; Bolívar, 2005; Regis Kabengele, 2018). The methodology employs exploratory, documentary, and bibliographic research, analyzing international official documents endorsed by international organizations and, at the national level, legislation addressing Special Education in Brazil. The results demonstrate that a society founded on humanist values is expected to promote inclusive educational systems in which students with disabilities can study in regular schools alongside other students. An educational system rooted in the concept of equity remains a challenge, requiring an understanding of schooling as a right recognized and guaranteed to all without distinction. It is also the State’s responsibility to implement public policies that respect differences and reduce inequalities within schools, fostering the construction of more equitable, egalitarian, and inclusive educational systems.